Oocyte zona pellucida dysmorphology is associated with diminished in-vitro fertilization success - Sauerbrun-Cutler, May-Tal (J Ovarian Res, 2015)
BACKGROUND: Although irregularities in human zona pellucida (ZP) morphology are well described, there is scant literature on the clinical significance of ZP dysmorphology. We, therefore, designed a retrospective cohort trial of ZP dysmorphology to assess the clinical significance of ZP dysmorphology and its affect on IVF outcome. Over the same time period a random sample of 77 cycles of 77 subjects with all normal oocyte morphology were selected as controls. METHODS: Between July 2006 and December 2010, all fresh non-donor cases performed at a university hospital IVF center were assessed for ZP dysmorphology. ZP dysmorphology included extracytoplasmic abnormalities (dark ZP and large perivitelline space) and oocyte shape (oval or irregularly shaped ZP). 136 IVF cycles from 119 subjects were identified where a majority of oocytes displayed ZP dysmorphology. Over the same time period a random sample of 77 cycles of 77 subjects with all normal oocyte morphology were selected as controls. IVF prognostic and outcome parameters were compared between the patients with dysmorphic and normal oocytes. RESULTS: 136/1710 (8.0%) cycles of fresh non-donor IVF displayed predominant ZP dysmorphology. Dysmorphic and normal oocytes showed no difference in the oocyte quality predictors such as FSH (6.03+/−2.5 vs. 6.8+/−2.3 IU/L), or AMH (2.5+/−2.0 vs. 2.30+/−1.5 ng/ml levels). ZP dysmorphology was associated with markedly diminished clinical pregnancy rates (44% vs. 70%; RR:0.62 [0.48, 0.80]; p = 0.0002), implantation rates (.17 vs. .36; IRR: 0.48 [0.34, 0.68]; p < 0.0001) and live birth rates as compared to non dysmorphic oocytes (29% vs. 52%; RR:0.55 [0.39, 0.79]; p = 0.001). CONCLUSIONS: ZP dysmorphology is associated with markedly diminished pregnancy and implantation rates in IVF. The poorer outcome appears to be independent of the usual markers of ovarian reserve.